A novel nonsense NBEAL2 gene mutation causing severe bleeding in a patient with gray platelet syndrome. (3rd April 2018) - Cao, Lijuan; Su, Jian; Li, Jiaming; Yu, Ziqiang; Bai, Xia; Wang, Zhaoyue; Xia, Lijun; Ruan, Changgeng
Abstract: Gray platelet syndrome (GPS) is a rare, inherited bleeding disorder characterized by the defect of platelet α-granule. Up to date, these are only four studies identifying NBEAL2 gene correlated with GPS. In the current report, we present a Chinese GPS patient who had severe bleeding tendency, abnormalities of platelet functions, and absence of platelet α-granules. Genomic DNA sequencing for the patient identified a nonsense mutation (g.27713C>A) of NBEAL2 gene (g.NG__031914.1) resulting in a premature protein (p.Glu1726*). In comparison with the reported patients, we conclude that homozygotes with nonsense or deletion mutation leading to a premature stop codon exhibit more serious bleeding problem than those with missense mutations.